2020
DOI: 10.1108/ijes-06-2019-0029
|View full text |Cite
|
Sign up to set email alerts
|

Stress in paramedics: relationships with coping strategies and personality traits

Abstract: PurposeThough working in the ambulance service implies persistent confrontation with human suffering and exposure to significant work-related stressors, previous research revealed comparatively low self-reported stress in paramedics. This study investigated stress, personality traits, sensation seeking and resilience in paramedics. Moreover, the impact of psychological variables on individual differences in paramedics' stress burden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…However, above all, Type D personality emerged as a specific and pivotal risk factor for nurses' psychophysical health, since it not only exacerbated the negative effects of work demands, but also it made ineffective the positive effects of work resources. These findings strongly confirmed the meaningfulness to also assess personality characteristics for a greater understanding of work‐related stress processes (Duschek, Bair, Haux, Garrido, & Janka, 2020; Parkes,1994; Tisu, Lupșa, Vîrgă, & Rusu, 2020), and clearly indicated the necessity to address, within counseling interventions, the significant role of Type D personality characteristics (i.e., negative affectivity and social inhibition; Mols & Denollet, 2010; Ogińska‐Bulik, 2006) in influencing nurses' perceived wellbeing.…”
Section: Discussionsupporting
confidence: 73%
“…However, above all, Type D personality emerged as a specific and pivotal risk factor for nurses' psychophysical health, since it not only exacerbated the negative effects of work demands, but also it made ineffective the positive effects of work resources. These findings strongly confirmed the meaningfulness to also assess personality characteristics for a greater understanding of work‐related stress processes (Duschek, Bair, Haux, Garrido, & Janka, 2020; Parkes,1994; Tisu, Lupșa, Vîrgă, & Rusu, 2020), and clearly indicated the necessity to address, within counseling interventions, the significant role of Type D personality characteristics (i.e., negative affectivity and social inhibition; Mols & Denollet, 2010; Ogińska‐Bulik, 2006) in influencing nurses' perceived wellbeing.…”
Section: Discussionsupporting
confidence: 73%
“…This suggests that many students may be better able to cope with the demands of the paramedicine profession upon employment. An individual's choice to pursue paramedicine is a decision to work in an environment where they will be frequently exposed to work-related stresses (Duschek et al, 2020). How well an individual copes in an environment where there is a high risk of developing PTSD, and where burnout is common, will depend to some degree on the protective influence of their personality (Kukowski et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Studies into coping strategies have identified that ambulance personnel use a variety of coping strategies to help them deal with the daily traumatic events they face. These coping strategies can be used before, during and after emergency cases (Mildenhall, 2012; Duschek et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%